Sams teach yourself Ajax, JavaScript, and PHP all in one - Ballard, Phil (Sams teach yourself all in one, 2009)
In just a short time, you can learn how to use Ajax, JavaScript, and PHP to create interactive interfaces to your web applications by combining these powerful technologies. No previous Ajax programming experience is required. Using a straightforward, step-by-step approach, each lesson in this book builds on the previous ones, enabling you to learn the essentials of Ajax programming with JavaScript, PHP, and related technologies from the ground up.